Application of PEM Fuel Cell for Stand-alone Based on an Fuzzy PID Control - Rakhtala, S.M.; Shafiee, E. (Institute of Advanced Engineering and Science, 2016)
Fuel cell (FC) systems are appropriate candidates as alternative energy sources for use in stand-alone applications. Due to the typical power profile of a stand-alone consisting of transients is not suitable for the use of a sole FC system. This paper presents the control of the fuel cell for stand-alone application based on fuzzy PID (FPID) controller. The aim of the paper is to achieve the control of the fuel cell for stand-alone by designing a suitable power conditioning unit that consists of the two stages of DC/DC converter and DC/AC inverter. A PID controller to be used for the voltage control of the designed boost converter is proposed and compared with a classical PID controller for performance validation. Furthermore, an analysis of double loop fuzzy PID controller for a single phase inverter is done.